The Role of Profit distribution policy in changing the shares' market value Case Study of Al Cham Islamic Bank's Share (Journal of Hama University, 2019)
This study aims to examine the role of the profit distribution policy in changing the market value of the company, applying to Cham Islamic Bank's share, one of the listed companies in the Damascus Stock Exchange.The researcher has measured the share price before the announcement of profits distribution, after the announcement of the distribution, and also has measured the share price before the actual distribution of profits and after it for a certain number of trading days in 2016 and 2017, based on the data published on the Damascus Stock Exchange website, then using the SPSS (V.24) by using the Paired Samples T Test to test hypotheses.The researcher has concluded that there is a significant difference between the market value of Al-Cham Islamic Bank's share, before announcing of profits distribution and after the announcement, and before the actual distribution of profits and after the actual distribution.